THE RELATIONSHIP OF MOM'S KNOWLEDGE ABOUT DENTAL CARE WITH THE EVENT OF DENTAL CARRIES IN CHILDREN AGED 3-6 YEARS - Atoilah, Elang Mohamad; Perceka, Andhika Lungguh (Jurnal Medika Cendikia, 2024)
Dental caries is one of the problems in health, especially in children. Parents, especially mothers, play an important role in developing children's positive behavior towards dental and oral health, parental participation in maintaining children's dental and oral health can be applied by paying attention to children's behavior regarding dental and oral health and children's eating patterns. The purpose of this study was to determine the level of knowledge of mothers about dental care with the incidence of dental caries in children. This study uses a quantitative approach design with a cross sectional design. This study used a sample of 43 respondents. The results obtained in this study showed a significant relationship between the mother's level of knowledge regarding dental care and the incidence of dental caries in children with p value = 0.000. Mothers who have a good level of knowledge about dental care have a small risk of their children experiencing dental caries.